The Existence of Minangkabau-Based Learning in Elementary Schools in Strengthening Local Wisdom - Infer, Beta Infertania Putri; Adrias, Adrias; Zulkarnaini, Aisy Putri (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2025)
Indonesia is widely recognized for its rich cultural diversity and indigenous customs and traditions. One of the most valuable local cultures is the Minangkabau natural culture, which has developed in the West Sumatra region. This culture contains values that serve as guiding principles in community life. This study investigates the significance of integrating Minangkabau-based learning in elementary schools. The purpose is to incorporate this cultural knowledge into elementary education and to understand the extent to which such learning is necessary for elementary students. The study adopts a quantitative method with a descriptive approach. The findings indicate that integrating Minangkabau-based learning in elementary schools is essential. This can be achieved by applying interactive teaching methods that enhance students' understanding, increase learning motivation, preserve local wisdom, and foster student character development. The study also reveals that effective implementation of Minangkabau-based learning requires interactive pedagogical methods and collaboration among various stakeholders, including government authorities, teachers, traditional leaders, and families.